What drives tax refund maximization from inter-temporal loss usage? Evidence from the German taxpayer panel - Clive Werdt (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2015)
This paper investigates the inter-temporal loss usage of tax units in Germany. Tax units that experience a loss in a year can offset that loss with positive income from adjacent year to receive a tax refund. Similar to companies, tax units can employ losses as carry-back in the year before the loss or as carry-forward in the year following the loss. The tax code does not force a particular loss usage but provides tax units with freedom to allocate the losses between carry-back and carry-forward. Choosing an individual appropriate allocation of carry-back and carry-forward creates a maximal tax refund. Intertemporal loss usage is a special case of tax avoidance: tax units receive a tax refund from loss usage as carry-forward (carry-back) but forfeit the alternative refund from carry-back (carry-forward). Estimations show that the probability of maximizing the tax refund highly depends on the difference of the tax rates from the loss adjacent years. An increase of 10 percentage points of the tax rate difference increases the probability of tax refund maximization by 24.5%. This confirms that tax avoidance is strong in case of significant tax incentives.
Keywords: H24; H63; D14; 330; losses; tax planing; taxpayer panel; administrative data